Allegorical Program for the Interior Decoration of the Kuskovo Palace: A Case Study of Interpretation - Kochetkova, Anastasia D. (Actual Problems of Theory and History of Art, 2023)
The article offers the interpretation and analysis of the symbolic subtext in the ceremonial interiors of the Large House of the Kuskovo Memorial Estate — a unique monument of Early Classicism with the original decoration preserved to this day. The study focuses on the subject-spatial context of the interiors, which includes architectural decoration, works of sculpture, painting, and decorative arts.The allegorical context of the interior decoration of the Large House consists of Bacchanalian and Anacreontic emblematics, as well as attributes of the sciences and arts. In this system particular attention is paid to the line of nature imitation. However, the main element in the figurative structure of the interiors is the panegyric trend, traditional for the Russian artistic practice of the 18th century, aimed at glorifying the imperial power and representatives of the Sheremetev family.The research of the allegorical program includes the works of French architects and decorators. This formulation of the problem allowed us to make some observations about the relationship of the Western European theory and national tradition in the field of interior decoration, as well as the role of architectural treatises in close connection with the role of a customer and the concept of a sample in the18th-century Russia.
Keywords: Classicism; Russian country estate; interior decoration; painting; sculpture; furniture; allegory; panegyric art; 18th century